Carbon stock assessment using forest canopy density mapper in agroforestry land in Berau, East Kalimantan, Indonesia - Adisti Permatasari Putri Hartoyo; Lilik Budi Prasetyo; Iskandar Zulkarnaen Siregar; Supriyanto .; Ida Theilade; Ulfah Juniarti Siregar (Society for Indonesian Biodiversity, 2019)
Abstract. Hartoyo APP, Prasetyo LB, Siregar IZ, Supriyanto, Theilade I, Siregar UJ. 2019. Carbon stock assessment using forest canopy density mapper in agroforestry land in Berau, East Kalimantan, Indonesia. Biodiversitas 20: 2661-2676. In the Reducing Emissions from Deforestation and forest Degradation (REDD+) program, remote sensing is the most important tool for measuring forest cover and carbon dynamic, including the utilization of software Forest Canopy Density (FCD) mapper. However, there have been rarely untested the accuracy of FCD applied in agroforestry landscapes to support carbon stock assessment compared to conventional field measurement data. This research was aimed to investigate the correlation between: (i) the value of FCD (%) and tree stand density (N/ha), (ii) the value of FCD (%) and basal area (m2/ha), (iii) the value of FCD (%) and total carbon stock (Mg C/ha), and iv) total carbon stock and percentage of canopy closure (%). Tree stand density, basal area, carbon stock and canopy profile were conventionally measured by trained members of local communities. The results of this study showed that the R2 between FCD and tree density was 37.7% (r = 61.4%), while the R2 between FCD and the basal area was 3.33% (r = 18.3%). The result of normality and heteroscedasticity tests showed that FCD was more accurate and precise in estimating the tree stand density model than the basal area model. Total carbon stock differed significantly (p<0.1) from tree density with R2 = 27.7% (r = 27.3%). Total carbon can be predicted using FCD with total carbon (Mg C/ha) = 13.005 + 0.826 FCD. Our findings suggest that FCD can be used as a new method to estimate tree density and total carbon stock cheaply, efficiently and accurately to support carbon stock assessment in agroforest practices. In carbon assessment, total carbon stock can also be estimated using canopy closure measurement.